2017
DOI: 10.1155/2017/5810372
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Quality of Reporting in Acupuncture Treatment Case Reports: An Analysis of the Core Journal in Korea

Abstract: Objectives The present study aimed to evaluate the overall quality of case reports concerning acupuncture treatment in Korea. Methods We selected a representative Korean journal and retrieved eligible case reports on acupuncture treatment published from 2009 to 2015. We assessed the quality of reporting based on CAse REport (CARE) and STandards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) guideline checklists. Results A total of 93 eligible case reports of acupuncture treatment were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…We found few reports focused on assessment of completeness of case reports. Most of them were from Asia regarding topics as acupuncture 9,10 . Eldawlatly et al evaluated completeness of case reports in the Saudi Journal of Anesthesia between 2013 and 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found few reports focused on assessment of completeness of case reports. Most of them were from Asia regarding topics as acupuncture 9,10 . Eldawlatly et al evaluated completeness of case reports in the Saudi Journal of Anesthesia between 2013 and 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them were from Asia regarding topics as acupuncture. 9,10 Eldawlatly et al evaluated completeness of case reports in the Saudi Journal of Anesthesia between 2013 and 2017. They concluded that the main topics they needed to make an improvement were patients' perspective and obtained consent.…”
Section: Introductionmentioning
confidence: 99%
“…Case reports not only guide personalised treatment in clinical practice, but also provide a precise means of recording diagnoses, principle treatments, outcomes, and prognoses [14]. Because case reports contain detailed clinical information about patients, they serve as valuable resources in patient-centred medicine [15]. Using previously published case studies, the presented case in the virtual diagnosis process could standardise and unify the information provided throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Virtual diagnoses have been employed to evaluate the clinical reasoning skill and diagnostic ability [14,15]. In accordance with previous studies, we followed the recent trend toward digital health by devising an online experiment for currently practicing doctors to collect medical information on patients.…”
Section: Introductionmentioning
confidence: 97%
“…. 2015년에는 Lee 등에 의해 CARE 지침의 한국 어판이 번역되어 보급되었으며 9) , 한의학 분야에서는 침 치료에 대한 증례보고의 질 평가 연구를 비롯하 여 10) , 대한한방소아과학회지 11) , 사상체질의학회지 12) , 한방비만학회지 13) , 동의신경정신과학회지 14) , 대한한 방부인과학회지 15) , 한방재활의학과학회지 16…”
unclassified